(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background Anemia represents a major healthcare burden in developing country like India. Since decades peripheral blood smear has been used for diagnosis of anemia. Cell counter has been introduced with increasing efficacy and a decreasing cost all over the world. Aim of this study was to correlate morphological typing of anemia based on RBC indices and RDW obtained from automated hematology analyzer with PBS (Peripheral Blood Smear) and to give better approach in diagnosis of anemia and analyze their limitations. Materials and Methods This prospective study was undertaken at Sir T hospital, Bhavnagar comprising of total 300 cases of anemia over a period of 4 months between July to October, 2021. Anemia typing was done by NIHONKODEN 9100 hematology analyzer and peripheral blood smear. Results Out of 300 cases, 265 cases of anemia typed by RBC indices and RDW obtained from hematology analyzer were correct. 35 cases needed blood smear examination for correct typing of anemia. Microcytic hypochromic anemia was the most common morphological type of anemia followed by normocytic normochromic anemia. Anemia was found to be more common in females. Microcytic hypochromic anemia and normocytic normochromic anemia was the most common type in females and males respectively. Conclusions PBS examination remains the gold standard test for morphological typing of anemia. With new advances in hematology analyzer typing of anemia can be done with indices and RDW but PBS confirmation is must. Both the methods should be used complementary to each other for better diagnostic accuracy.